POLA PERILAKU SANTRI PUTRI DI PONDOK PESANTREN DAR EL HIKMAH (Analisis Dramaturgi Dalam Kehidupan Pondok Pesantren) - Desmayesi "; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted at the Dar El Hikmah Islamic Boarding School in Pekanbaru with the purpose to find out the behavior of female students of Madrasah Tsanawiyah when in the back room and in the public stage of the school (front stage) in dramaturgy analysis. In this study using descriptive qualitative research methods. Subjects in this study were 5 female students as subjects and 2 teachers as informants. In collecting data using observation techniques, in-depth interviews and documentation. The results in this study indicate that the behavior of female students when they are in a back stage dormitory is different from the behavior when in a public school space. When students are in the private room of the hostel many violations occur, such as speaking harshly, dirty, and indecent, dont use official Arabic and English, sexy dress or dont comply with the rules, dont obey the existing rules. But it is different when students are in public spaces of the school they will try to build themselves, put themselves down by giving a good impression as if they are obedient and obedient to follow any existing rules. Keywords: Dramaturgy, Patterns of Behavioral, Female Students